Secrecy, Community and Counter-History in Arundhati Roy’s ’The God of Small Things’ (1997) - Valero Redondo, María (Complutense Journal of English Studies, 2020)
This article explores the different types of communities and the role of secrecy and counter-history in Arundhati Roy’s The God of Small Things (1997), a novel in which secrecy plays a crucial role and in which the most genuine human relations are characterized by a desire to participate in otherness. This article examines Roy’s subversion of the operative community by considering: (a) the different communitarian organizations in The God of Small Things, from the most organic (the caste system, patriarchy, religious institutions, communism and the commodification of culture) to the least organic (the community of Others and the community of lovers); (b) the connection between alterity, finitude and secrecy as preventing the unworked community from organicist fusion; (c) the link between alterity, finitude, secrecy and counter-history. Although ingrained within a deeply organicist community, the main characters in Roy’s novel prove to have a vigorous capacity to trespass communitarian boundaries and to expose themselves to otherness.